The South Beach Diet : The Delicious, Doctor-Designed, Foolproof Plan for Fast and Healthy Weight Loss - Agatston, Arthur M.D. (New York Rodale, 2003)
A renowned cardiologist discusses the importance of understanding the glycemic index values of foods and presents a weight-loss program that includes meal plans and recipes.
Include Index
Keywords: Reducing Diets -- Glycemic Index